Cep63 recruits Cdk1 to the centrosome: letter - Alsara, Mohammad; Löffler, Harald; Fechter, Anne; Bartek, Jiri; Krämer, Alwin (Cancer research, 2015)
In 2011, we published a characterization of the phenotypes of Cep63 downregulation and overexpression in human cells in Cancer Research ([1][1]). Recently, it was shown that several antibodies commonly used to detect Cdk1 cross-react with Cep152 ([2][2]). In our article, we used one of these